2019
DOI: 10.1016/j.eucr.2019.100844
|View full text |Cite
|
Sign up to set email alerts
|

Female urinary retention from a huge periurethral mass caused by immunoglobulin G4-related disease (IgG4-RD)

Abstract: Immunoglobulin G4-related disease is a systemic disease, recognized as extensive T-lymphocyte and IgG4-positive plasma cells. It can present as inflammatory pseudotumor in various organs. A female 75 years old, diagnosed IgG4-related autoimmune pancreatitis, presented with urinary retention. Pelvic examination showed well-defined, soft tissue mass, bulging from anterior vaginal wall. MRI pelvis demonstrated a huge periurethral mass, size 6.2 × 4.4 × 4.2 cm, encasing the urethra, extending from bladder neck to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Hensley et al reported significant objective response with crizotinib in a 39-year-old male with diffuse metastatic disease ( 14 ). A patient who declined surgical treatment was treated with corticosteroids and azathioprine, however, no follow-up information was provided ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hensley et al reported significant objective response with crizotinib in a 39-year-old male with diffuse metastatic disease ( 14 ). A patient who declined surgical treatment was treated with corticosteroids and azathioprine, however, no follow-up information was provided ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed 19 IgG4-related IPTs that occurred at uncommon sites (fewer than 3 cases reported) (Table ) [please check this carefully] (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The lesions were located at the breast in three cases, epidural in two cases, mediastinum in two cases, paratestis in two cases, urethra in two cases, and oral cavity, trachea, adrenal gland, bladder, rectum, abdominal wall, pericardium, uterine in one case each.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-RD is diagnosed when the following criteria are met: (i) clinically enlarged mass, nodule, or hypertrophic lesion in single or multiple organs; (ii) serum IgG4 level of at least 135 mg/dL; and (iii) cell infiltration, IgG4/IgG-positive cell ratio >40% on high-power field. 1 The female urethra has not been described as a preferred site for IgG4-RD, and there has only been one case, reported by Choi et al, 2 and Sangsoad et al 3 Patients may either present with symptoms, as in Case 1, or be asymptomatic with multiple organ involvement, as in Case 2.…”
Section: Discussionmentioning
confidence: 99%